Bibliometric Insights into Women Entrepreneurship : A Global Perspective on Key Contributions and Challenges - Loso Judijanto; Ivon Arisanti (West Science Journal Economic and Entrepreneurship, 2024)
This study employs a comprehensive bibliometric analysis to explore the landscape of research on women's entrepreneurship using VOSviewer software. Through a series of visualizations, we examine the co-authorship networks, key thematic focuses, geographical distributions, and the temporal dynamics of the field from 2000 to 2022. Our findings reveal significant collaborative dynamics among scholars, with central figures acting as pivotal nodes in the academic network. Thematic analysis highlights "women empowerment," "SMEs," and "entrepreneurship" as foundational research areas, alongside emergent topics like "digital entrepreneurship" and "COVID-19," which respond to contemporary global challenges. Geographical visualization underscores the global reach and diversity of the research, with notable contributions from across various continents. The study’s temporal overlays demonstrate the field’s adaptability to shifting global economic and social contexts, particularly in response to the pandemic. These insights not only reflect the current state of women's entrepreneurship research but also suggest directions for future inquiry, emphasizing the need for enhanced international collaboration and adaptation to emerging global trends. This work contributes to the strategic development of women's entrepreneurship research, offering a scaffold from which to enhance academic collaborations and integrate emergent research themes effectively.